Investigating age-related muscle force adaptations in males and females during sit-to-walk transition motion using EMG-informed modeling - Hussain, Zakia; Gopalai, Alpha Agape; Ahmad, Siti Anom; Salim, Mazatulfazura Sf; Gouwanda, Darwin; Teh, Pei Lee (Elsevier B.V., 2025)
Background: The sit-to-walk (STW) transition is essential for mobility but deteriorates with age due to declining muscle strength, balance, and postural control. This study hypothesizes that age- and sex-related variations in muscle forces during STW lead to altered muscle recruitment strategies, reflecting compensatory mechanisms. When these compensations are no longer adequate, mobility limitations may occur. Methods: This study involved 65 healthy adults (32 males and 33 females) from three age groups. Motion capture and surface electromyography (sEMG) data were used to develop an EMG-informed neuromusculoskeletal model for estimating muscle forces. Age and sex-related variations in muscle forces were analyzed using Generalized Linear Mixed Modeling (GLMM). Results: The findings reveal consistent recruitment of primary STW muscles across all age-sex subgroups. The vasti, gluteus maximus, gluteus medius, dorsiflexors, and soleus generated the highest average muscle forces during STW. However, older adults consistently generated lower forces in these muscles during rising (except for the soleus). Despite this, phase durations were like other groups, with increased ankle plantarflexor (except gastrocnemius) and hip abductors (gluteus medius) forces to support gait transition. These findings indicate compensation in healthy aging involves variations in muscle force production rather than altered muscle recruitment strategies. Moreover, females exhibited more pronounced age-related muscle force changes than males during gait initiation. Conclusion: Significant age- and sex-specific variations in muscle forces across STW phases highlight the need for biomechanically informed interventions to preserve muscle health and reduce functional decline. Targeted interventions should focus on strengthening STW muscles and not just knee extensors to enhance mobility. For example, exercises like Tai Chi, known to improve dynamic stability during gait initiation, can benefit females across age groups.